The Master Key of the Ozone Therapy in Russia Dr. Sergei Petrovich Peretyagin (Ozone Therapy Global Journal, 2017)
Dr. Sergei Petrovich Peretyagin may be considered the master key for the development of ozone therapy in Russia. He founded the Nizhny Novgorod Interregional Ozone Therapy Center; and the Russian Association of Ozone Therapy. The Russian Federal Service Control of Health and Social Development of the Ministry of Health authorized the use of medical ozone in obstetrics, gynecology and neonatology; on traumatology; and on dermatology and cosmetology. Russia has accepted ozone therapy as a normal practice in its medical centers and to be teaching at the university and post-graduate level. Author of more than 250 scientific publications, 18 inventions and 20 rationalization proposals. Dr. Peretyagin was awarded the Honorary Diploma of the Russian Minister of Health. .